Multilateral Environmental Agreements and the Trade Measures Contained in These Agreements - Margareta Timbur (CES Working Papers, 2012)
The environmental problems which the society is facing, ozone depletion, biodiversity loss, the spread of persistent organic pollutants, are a result of human activity with a worldwide impact, requiring immediate resolution. In this context, negotiation, signing and implementation of several multilateral environmental agreements (MEAs) are one of the best solutions, affordable and reliable. The aim of this study is to analyze the commercial measures, which to some extent, ensure stability, security, and expansion of MEAs. The paper discusses, also, the efficiency, necessity and the influences of trade measures in MEAs and the WTO role in signing these agreements.
Keywords: F18; Q34; Q56; Q57; 330; multilateral environmental agreements; trade measures; TBT and SPS Agreements; WTO Romania